2017
DOI: 10.1002/bjs.10445
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and trial sequential analysis of triclosan-coated sutures for the prevention of surgical-site infection

Abstract: Background: Triclosan-coated sutures (TCS) were developed to reduce the risk of surgical-site infection (SSI). Level 1A evidence of effectiveness has been presented in various recent meta-analyses, yet well designed RCTs have not been able to reproduce these favourable results. The aim of this study was to evaluate all available evidence critically with comprehensive analysis to seek a more reliable answer regarding the effectiveness of TCS in the prevention of SSI.Methods: PubMed, MEDLINE, Embase and Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 70 publications
(396 reference statements)
4
49
0
1
Order By: Relevance
“…TCS materials were used explicitly for tissue closure in the postchange cohort, a decision that was based on recent CDC and World Health Organization (WHO) meta‐analyses and systematic reviews that reported a statistically significant decrease in SSI in both humans and animal models regardless of the type of procedure . TCS products have been found to inhibit bacterial adherence and the growth of several bacterial species that cause SSI, particularly methicillin‐resistant and non–methicillin‐resistant S. spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCS materials were used explicitly for tissue closure in the postchange cohort, a decision that was based on recent CDC and World Health Organization (WHO) meta‐analyses and systematic reviews that reported a statistically significant decrease in SSI in both humans and animal models regardless of the type of procedure . TCS products have been found to inhibit bacterial adherence and the growth of several bacterial species that cause SSI, particularly methicillin‐resistant and non–methicillin‐resistant S. spp.…”
Section: Discussionmentioning
confidence: 99%
“…TCS products have been found to inhibit bacterial adherence and the growth of several bacterial species that cause SSI, particularly methicillin‐resistant and non–methicillin‐resistant S. spp. that make up the normal flora of the skin in dogs …”
Section: Discussionmentioning
confidence: 99%
“…Since then a large number of randomised controlled trials (RCTs) have been performed with contrasting results of the effectiveness of triclosan-coated sutures in the prevention of SSIs. Subsequent meta-analyses have also produced conflicting results and hence the true effect remains unclear 6 7 27–32. The most recent and largest systematic review to date was performed by de Jonge et al and found triclosan-coated sutures significantly reduced the incidence of SSIs 32.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent meta-analyses have also produced conflicting results and hence the true effect remains unclear 6 7 27–32. The most recent and largest systematic review to date was performed by de Jonge et al and found triclosan-coated sutures significantly reduced the incidence of SSIs 32. This review searched the literature up until November 2015 and included 6462 patients from RCTs published in peer-reviewed journals as well as conference abstracts.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical techniques may be able to reduce the SSI rate, and ideal approaches have long been examined, including antimicrobial suture and methods of abdominal closure . However, these previous reports have focused on open colorectal surgery, and there are few reports of risk factors for incisional SSI with laparoscopic colorectal surgery (Lap CR).…”
Section: Introductionmentioning
confidence: 99%